THE UNDERLYING REASONS OF TEACHERS’ MANIPULATION IN TEACHING PROCESS - Lenny Bey B; Berlin . Sibarani; Immanuel Prasetya Gintings (LINGUISTIK TERAPAN, 2023)
This research investigated the reason why the teachers did manipulation in teaching. The study applied qualitative descriptive method. The participants of the research were three teachers that have different background. The techniques for collecting data were through recording three teachers in teaching descriptive text elements and interviewing three teachers. There are some reasons found why teachers manipulate because of presage variable such as teaching experience, belief in their skill in knowledge, belief in their skill in teaching that can influence process variable. It also influenced by context variable such as the students are lack of interest, less motivation and have different background that can support them to learn English and both variables also influence process variable as teaching process does not run well because in process there were students’ weakness, students’ minimal response even they did not give response and feedback in teaching process.